KOMPARASI ANALISIS GEROMBOL (CLUSTER) DAN BIPLOT DALAM PENGELOMPOKAN - ARIAWAN, I MADE ANOM; KENCANA, I PUTU EKA NILA; SUCIPTAWATI, NI LUH PUTU (E-Jurnal Matematika; Vol 2 No 4 (2013), 2013)
One of functions of multivariate analysis is to group data. Multivariate analysis often used in grouping  data are cluster analysis and biplot analysis. In this paper, a comparative analysis will be made between clusters analysis and biplot analysis  for grouping the data. Technique used in the cluster analysis is k-mean method  and biplot analysis used two-dimensional display.  The results ware that biplot analysis produces are better in grouping accuracy than clusters analysis. But in general, biplot analysis can not be said to be better than clusters analysis in grouping the data and vice versa.
Keywords: comparative; multivariate analysis; clusters analysis; biplot analysis